Policies to promote shipping registration in Singapore - PHANG, Sock Yong (Institutional Knowledge at Singapore Management University, 1994)
An analysis traces the development of ship registration in Singapore and examines the underlying motivation behind changes in policies over the last 3 decades. For the better part of the 1970s Singapore was classified as a flag of convenience (FOC) country as it pursued an FOC policy that emphasized the quantitative growth of its merchant fleet. Beginning in 1979 Singapore tightened maritime standards as well as ownership disclosure rules, requiring a foreign shipowner to incorporate a company in Singapore. It is regarded today as a quasi-FOC country - a term associated favorably with countries offering tax incentives to shipowners. The objective of recent tax policy in the form of the Approved International Shipping Enterprise Scheme (1991) is to provide incentives for international shipping companies to use Singapore as their base of operations. This is to facilitate the development of Singapore as an international maritime center.